Tacrolimus Intrapatient Variability After Switching From Immediate or Prolonged-Release to Extended-Release Formulation, After an Organ Transplantation - Del Bello, Arnaud; Gaible, Clotilde; Longlune, Nathalie; Hebral, Anne-Laure; Esposito, Laure; Gandia, Peggy; Kamar, Nassim (Frontiers in Pharmacology, 2021)
Background and Purpose: Several formulations of tacrolimus are available, but evidence of the benefit of changing to the most recent formulations is lacking. Tacrolimus intra-patient variability (tacrolimus IPV) is an emerging risk factor associated with poor graft outcomes after solid organ transplantations. Here, we examined the modifications of tacrolimus IPV after switching to a different formulation of tacrolimus. Experimental Approach: We identified 353 solid organ transplant recipients that were switched in our center from immediate-release (IR-tacrolimus) or prolonged-release tacrolimus (PR-tacrolimus) to extended-release, LCP-tacrolimus (LCP-tacrolimus). Among them, 54 patients underwent at least 3 available tacrolimus blood concentrations before and after the switch, allowing us to investigate tacrolimus IPV. Key Results: The switch was considered as a safe procedure since only four of the 353 patients presented a graft rejection after the switch, and no patient was hospitalized for tacrolimus overdose. The tacrolimus IPV estimated by the coefficient of variation (CV-IPV) was stable before and after the switch to LCP-tacrolimus (CV-IPV: 29.0% (IQR 25–75 (15.5; 38.5) before and 24.0% (15.8; 36.5) after the switch, p = 0.65). Conclusion and Implications: Switching from IR- or PR-tacrolimus to LCP-tacrolimus is a safe procedure. However, the CV-tacrolimus IPV was not impacted by the change of formulation.